Prospects for biological therapy in severe pediatric asthma - Khamzaeva , Kamina (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The article discusses current possibilities and prospects for using monoclonal antibodies (anti-IgE, anti-IL5/4/13 therapy) in children with severe asthma resistant to standard treatment. Data on the efficacy of targeted drugs in reducing hospitalization rates and systemic steroid dependence are presented.